Urban agriculture: a way forward to food and nutrition security in Malaysia - Rezai, Golnaz; Shamsudin, Mad Nasir; Mohamed, Zainal Abidin (Elsevier, 2016)
The practice of urban agriculture has gained importance due to the rising rate of urban poverty and population in the developing regions. In countries such as Malaysia, it also addresses food security by providing the urban dwellers with access to adequately nutritious, safe, acceptable and cost-effective food. While there are some skepticism toward urban agricultural activities in providing food for the urban markets, this study has nevertheless explored the existing evidence of its effectiveness in providing food security among urban dwellers and consequently reducing a large share of their food bills. Interviews of 360 households shown a positive statistical association between obtaining a sufficient quantity of food and adequate diet through engagement in urban agriculture. The results from this study indicate that food security can be derived from urban agriculture since it provides sufficient quantities of food, appropriate nutrition, cost-effective food supplies and reduction in food bills. This highlights the need for the Malaysian urban authorities to give more appropriate recognition and contribution to city dwellers and encourage them to expand the practice of urban agriculture.